Issuance and valuation of corporate bonds with quantitative easing - Stefano Pegoraro; Mattia Montagna (European Central Bank (ECB), 2021)
After the announcement of the European Central Bank's corporate quantitative easing program, non-financial corporations timed the bond market by shifting their issuance toward bonds eligible for the program. However, issuers of eligible bonds did not increase total issuance compared to other issuers; nor did they experience different economic outcomes. Instead, the announcement produced substantial spillover effects on risk premia. Credit risk premia declined, both in the corporate bond market and in the default swap market, whereas the valuation of eligible bonds did not change relative to comparable ineligible bonds. Firms took advantage of reduced risk premia by issuing riskier bond types. Using a novel and comprehensive dataset of corporate bonds in the euro area, we document how firms substituted across bond characteristics, and we find evidence of their intention to time the market. Our model indicates corporate market timing is instrumental in allowing quantitative easing to produce spillover effects.
Keywords: G32; G12; E52; E58; E44; 330; Quantitative easing; corporate bonds; market timing; risk premia; CSPP